SURVEI TINGKAT KETERAMPILAN MOTORIK DALAM BERMAIN GAME ONLINE PADA SISWA KELAS 5 SDN - Subuhu Salam; Samsudin; Sri Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the fine motor skills level of fifth-grade students at SDN 7 Sape who actively play online games and to identify the relationship between playing intensity and their motor skills. This research employed a quantitative approach with a descriptive-exploratory survey design. The sample consisted of 15 students selected purposively based on the criterion of playing online games at least three times a week. Data were collected through an online gaming habit questionnaire, fine motor skill tests, and direct observation, then analyzed using descriptive statistics and Pearson correlation tests. The results showed an average fine motor skill score of 38.2 out of a maximum score of 50, categorized as good. Most students were in the good category (40%) and very good category (20%), with well-trained hand–eye coordination and finger reaction speed. However, accuracy and neatness remained weaknesses, with only 47% of students achieving a good category. These findings indicate that online games can positively contribute to visual coordination and reaction speed if played in reasonable durations and with supervision, but do not fully develop motor skills requiring precision and slow movement control. The study recommends regulating playing time, selecting educational games, and increasing creative physical activities to support comprehensive motor skill development.